A CT-based examination of first-class meat parts in different sheep genotypes - Kupai, Tímea; Lengyel, Attila; Toldi, Gyula (Acta Agraria Kaposváriensis, 2002)
The tissue components offirst-class meat parts of ram and ewe lambs of four genotypes (lie de France, Hungarian Merino, Suffolk and Pannon Meat Sheep) in 30 ± 3 kg live weight were compared (10 animals per categories, altogether 80 animals). We demarcated the area of the tissue of first-class meats on that images, which are included these meat parts. The examinations were carried out with the help of statistical tests that were made on the basis of CT images. Concerning the fat deposition of each first class meat part, the order of the breeds was the same (Merino, lie de France, Pannon Meat Sheep and Suffolk), which can be proven statistically. The Merino deposed three times more fat than the Suffolk. The fat deposition of the ewes is more intensive than that of the rams, however, there is a slim difference between the two sexes in meat types. We did not observe significant differences in meat area of the different breeds. The Suffolk was prominent among the others because of its small quantity of water-like materials. In order to use better the growth potential of the meat type sheeps and their FI lambs, the increased utilisation of the advantages provided by the slaughter weight over 30 kg is advisable.
Keywords: CT; examination; first class meat parts; sheep genotypes